Effect of Electrostatic Interactions in the Separation of Magnetite and Silica using Enhanced Gravity Concentration - Baladad, Karlo Leandro; Tungpalan, Djoan Kate; Mendoza, Herman (Philippine Engineering Journal; Vol 43 No 2 (2022), 2022)
This study investigates the effect of electrostatic interactions in the separation of magnetite and silica in aqueous media using enhanced gravity concentration. As the effect of electrostatic interactions becomes more prominent in finer size ranges, understanding this correlation can help in determining what conditions will improve the performance of enhanced gravity concentrations. Magnetite and silica suspensions at different coagulation conditions were prepared and subjected to enhanced gravity concentration using a Falcon L40 concentrator. The resulting separations were then related to the observed coagulation responses.   The zeta potential of magnetite as a function of pH and electrolyte concentration was measured using an electrophoretic method and the critical coagulation concentration of magnetite was determined using a UV-VIS Spectrometer. The total potential energy curves generated from the zeta potential and CCC data, showed the dominant forces that affect coagulation behavior at various pH levels. Repulsive forces were found to be most dominant at pH 11 for both magnetite-magnetite and magnetite-silica suspensions. Increased recovery of both magnetite and silica was observed at pH 3 where attractive forces are strongest both for one-component and two-component interactions. However, the increased recovery of both particles resulted in decreased separation efficiency at this condition. At pH 11, where repulsive forces are dominant for both one-component and two-component interactions, recovery of both particles decreased. The highest separation efficiency 64.1% was at pH 9. At this condition, magnetite-silica interactions were repulsive which led to the increased removal of silica. The attractive one-component interaction of the remaining magnetite particles led to its increased agglomeration and subsequently, increased magnetite recovery and grade at this condition.   Keywords: Enhanced Gravity Concentration, Electrostatic Interactions, Falcon Concentrator, DLVO Theory, Zeta Potential